Elected Without Buying Vote: Woman Candidate, Canvassing, and Programmatic Campaign in the 2019 Local Legislative Election - Rohman, Noor; Holilah, Holilah (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2021)
Although extensive studies have been carried out on women candidates in the Indonesia election, no specific attention discusses elected women candidates without relying on vote-buying. This paper seeks to explain how and to what extend the winning strategy of a woman candidate elected with limited financial resources. We argue that door to door canvassing and programmatic campaign through social media are a crucial alternative strategy for a woman candidate to mobilize voters. The argument builds based on the case study of an elected woman candidate from the Indonesian Solidarity Party at district 10 of the Jakarta provincial parliament. This article shows that a woman candidate prioritized personal communication with voters directly and policy program campaign as a central winning strategy. There is a more optimistic story about an elected woman candidate in the local legislative election when compared to previous studies. Our findings confirm that a woman candidate could secure the parliament seat without relying on vote-buying, political dynasty, and male power.